2022
DOI: 10.1101/2022.11.17.515635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hamsters are a model for post-COVID-19 alveolar regeneration mechanisms: an opportunity to understand post-acute sequelae of SARS-CoV-2

Abstract: A relevant number of coronavirus disease 2019 (COVID-19) survivors suffers from post-acute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (PASC). Current evidence suggests a dysregulated alveolar regeneration in COVID-19 as a possible explanation for respiratory PASC symptoms, a phenomenon which deserves further investigation in a suitable animal model. This study investigates morphologic and transcriptomic features of alveolar regeneration in SARS-CoV-2 infected Syrian golden hamster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
(208 reference statements)
2
7
0
Order By: Relevance
“…The findings are consistent with those reported in hamsters 4 days after wildtype SARS-CoV-2 infection [20]. In three animals there were changes consistent with early regenerative attempts, i.e., mild hyperplasia of type II pneumocytes/bronchiolar epithelial cells (Figure 6A); these have previously been reported to be present already at this timepoint [20,21]. All donors exhibited degeneration of respiratory epithelial cells and a variably intense neutrophil-dominated rhinitis, in which the detection of viral N-RNA and/or NP confirmed the infection.…”
Section: Pathological Changes In the Lungs And Nasal Mucosasupporting
confidence: 90%
See 2 more Smart Citations
“…The findings are consistent with those reported in hamsters 4 days after wildtype SARS-CoV-2 infection [20]. In three animals there were changes consistent with early regenerative attempts, i.e., mild hyperplasia of type II pneumocytes/bronchiolar epithelial cells (Figure 6A); these have previously been reported to be present already at this timepoint [20,21]. All donors exhibited degeneration of respiratory epithelial cells and a variably intense neutrophil-dominated rhinitis, in which the detection of viral N-RNA and/or NP confirmed the infection.…”
Section: Pathological Changes In the Lungs And Nasal Mucosasupporting
confidence: 90%
“…With the nafamostat treatment, two thirds of the sentinel animals tested negative by all approaches at 4 dpi, and there was generally no viral antigen detected. However, several of these animals showed focal type II pneumocyte/bronchiolar epithelial cell hyperplasia, which is consistent with regenerative attempts after infection, as it can be seen as early as 3 days post infection in the hamster model of COVID-19 [20,21]. Some discrepancies were observed between the results of the different approaches to detect and quantify infection.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Despite viral clearance, both the olfactory bulb and olfactory epithelium exhibited myeloid and T-cell activation, proinflammatory cytokine production, and an interferon response [68]. Another hamster model study indicated that SARS-CoV-2 infection induced dysregulated alveolar regeneration and subpleural fibrosis [107].…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Blood vessels as well as artifacts were subtracted from the total lung tissue as they were indicated as ROIs. Automated positive cell detection was used, as previously described [14], to quantify the immune-stained cells in the lung tissue. This was based on marker-specific thresholding parameters.…”
Section: Introductionmentioning
confidence: 99%